A Semantic Interpretation of W. B. Yeats' "The Second Coming " and "Leda and The Swan "in Terms of The Employed Mythical / Archetypal Lexical Items - Abdul Razzaq Darwish Abdul Razzaq (Thi Qar Arts Journal, 2020)
The present study aims at presenting a semantic interpretation of William Butler Yeats' "The Second Coming" and " Leda and The Swan" in terms of the significance of the employed mythical/archetypal lexical items . The Mythical/Archetypal Approach depends on the works of C. G. Jung and Joseph Campbell .This approach is to be followed in highlighting the significance of the mythical /archetypal employment as it is expressed through the lexical items mentioned in the two poems. The interpretation of "The Second Coming "and "Leda and The Swan" is given with reference to the significant recurrence of certain lexical items that have  mythical /archetypal indications. The paper contains an overview about the role of myth in literature in general and in W.B. Yeats' poetry in particular .The lexical items that have mythical indications are of different references : religious, political , and historical .The association between the lexical items  mentioned in both of the poems and the mythical /archetypal meaning shows a creative way to convey the themes of these poems . The paper ends up with some conclusions, appendices , and a list of references.